Identification of Risk Factors in Cervical Cancer (Indian Journal of Public Health Research & Development, 2020)
Background: The prevalence of cervical cancer was about 528.000 cases with mortality rate of 266.000around the world and was ranked first as the most female genital cancers in developing countries. One ofthe factors suspected to be the cause of cervical cancer is the long-term use of hormonal contraception. Thisresearch aimed to identify risk factors of cervical cancer in General Hospital of Dr. Soetomo Surabaya.Method: Analytical retrospective study with case control method was used in this study. Information aboutcontraception use and other risk factors was obtained from personal interview. Sampling was done byaccidental sampling technique. The sample meeting the inclusion and exclusion criteria was divided intotwo groups, namely 124 case groups and 124 control groups. The data was analysed using chi-square test and logistic regression.Result: Patient using oral contraception for more than 5 years showed the results of OR 5.410; 95% CI =2.403-12.176 and patient using Intrauterine Device (IUD) for more than 5 years had OR 3.016; 95% CI =1.122-8.113. While prim-gravida age under 20 years was OR 2.621; 95% CI = 1.465-4.688. This data wascontrast if compared with female having prim-gravida age above 20 years.Discussion: Theoretically, the use of the hormonal contraception causes cancer. It is correlated withexistence of oestrogen and progestin hormone’s role to increase the protein expression of E6 and E7 fromHPV. Moreover, young age is indicated to have the condition of intimal genital cells which are immature, sothat if pregnancy occurs, it can induce a cell damage and facilitates genital infection.Conclusion: The use of oral combination contraception and non-hormonal contraception more than 5 yearsand prim-gravida age is under 20 years are dominant factors influencing cervical cancers in woman
Keywords: Cervical Cancer, Risk Factors, Oral Contraception, Prim-gravida